1997
DOI: 10.1046/j.1365-4362.1997.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforating granuloma annulare

Abstract: PGA is different to GA not only histologically but also clinically. It is a disseminated disease, affecting both children and adults, which is characterized by the presence of multiple papules, most of them umbilicated and/or crusted, and characteristically pustular lesions and scars. Histology suggests that the superficial localization of the necrobiotic granuloma leads to the epidermal perforation. Treatment is disappointing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 36 publications
4
64
0
2
Order By: Relevance
“…In an article published by Pablo F. Peñas et al, it is observed that in the generalized form, pustuliform lesions and scarring appear in significantly higher percentages than in the localized and perforating variants. 3 In the case that we reported, defined as a generalized and perforating form, the patient showed the initial characteristics of most lesions in the pustular lesion, a fact which reinforces the findings of the literature. 3 Harsch Mohan et al published a study with 586 cases of granulomatous dermatitis, of which 71 (12.11%) were classified as non-infectious granulomas by means of clinicopathologic analyses.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In an article published by Pablo F. Peñas et al, it is observed that in the generalized form, pustuliform lesions and scarring appear in significantly higher percentages than in the localized and perforating variants. 3 In the case that we reported, defined as a generalized and perforating form, the patient showed the initial characteristics of most lesions in the pustular lesion, a fact which reinforces the findings of the literature. 3 Harsch Mohan et al published a study with 586 cases of granulomatous dermatitis, of which 71 (12.11%) were classified as non-infectious granulomas by means of clinicopathologic analyses.…”
Section: Discussionsupporting
confidence: 89%
“…3 The average age of onset is higher among diabetic patients, which is around 33 years for the generalized form. 7 The case that we described had a delayed onset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations